PENGARUH STORE ATMOSPHERE, KUALITAS PELAYANAN DAN CITA RASA TERHADAP MINAT BERKUNJUNG KEMBALI DI AMING COFFE PODOMORO - Yonas Saputra; Ery Niswan; Naiyun Untung Utama (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2023)
This research was conducted to determine the effect of store atmosphere, servicequality and taste on the intention to return to Aming Coffee Podomoro. The research method used is aquantitative method with a descriptive research type. The population in this study were visitors toaming coffee who had visited at least 3 times 115 people and the sampling technique used was nonprobability sampling method with purposive sampling technique. The data analysis method used is thevalidity test, reliability test, the analysis phase uses multiple linear regression and hypothesis testing uses the SPSS 23 program for windows.The results of this study indicate that the variable store atmosphere, service quality and tastehave a positive and significant effect on the intention to return to Aming Coffee Podomoro,simultaneously by 69.5%, while the remaining 30.5% is influenced by other factors outside the studyThis. Store atmosphere, service quality and taste variables have a positive and significant effect on theintention to revisit Aming Coffee Podomoro